Regional Tax Externality and Competition: Empirical Study in Early Decentralization Era of East Java Province - Rifa'i Afin (MediaTrend, 2018)
This paper concerned with the empirical study about tax competition among regions which in a theoretical point of view, tax competition is seen as an economic policy strategy to attract mobile tax bases and firms in order to boost economic development in terms of employment and output growth within the political jurisdiction implementing it. Using a panel of more 400 observed district and municipal inEast Java. It provides empirical evidence on how the local tax as well as the retribution in the neighborhood affect the local tax. The results support the existence of fiscal externalities: an increase in the tax and retribution of local neighbors exerts a positive effect on the local tax which is shown by spatial weighting variable both tax and retribution. Several factors that are hypothesized affect local tax also significant to determine local tax, these factors such as original regional income, and regional domestic product as a proxy of income.